Human Toxocariasis: Presenting a Case Report of Eosinophilic Myocarditis Associated with Toxocara canis Infection and a Literature Review - Anna Nikopoulou; Lazaros Sideras; Athanasia Marina Peristeri; Panagiota Ligda; Olympia Akritidou; Smaragda Sotiraki (Microbiology Research)
Toxocariasis is a parasitic zoonosis caused by ascarid nematodes of dogs (Toxocara canis) or cats (Toxocara cati). Transmission to humans can occur in various ways, most commonly through the ingestion of infective embryonated eggs in soil or on vegetables or fruits and less frequently through ingestion of raw or undercooked meat contaminated with larvae. The disease manifestations span a broad clinical spectrum, ranging from asymptomatic seropositivity to severe systemic complications including sepsis and septic shock, with the presentation varying according to the affected organ systems. Cardiac involvement is a rare but potentially life-threatening complication and consists of myocarditis, pericarditis or Loeffler’s endocarditis (eosinophilic myocarditis). We present a case of eosinophilic myocarditis associated with Toxocara canis infection in a 54-year-old woman living in a rural area near the forest and provide a brief review of the literature.